Benefits and barriers to participating in longitudinal research of youth-onset type 2 diabetes: Results from the TODAY retention survey. (April 2016) - Walders-Abramson, Natalie; Anderson, Barbara; Larkin, Mary E; Chang, Nancy; Venditti, Elizabeth; Bzdick, Suzan; Tryggestad, Jeanie B; Tan, Kenny; Geffner, Mitchell E; Hirst, Kathryn
Background/Aims: Conducting longitudinal research related to chronic illness in adolescents is inherently challenging due to developmental changes and psychosocial stressors. Participants in the Treatment Options for type 2 Diabetes in Adolescents and Youth clinical trial were socioeconomically disadvantaged as well. This study assessed attitudes and beliefs about retention in Treatment Options for type 2 Diabetes in Adolescents and Youth to shed light on the factors that potentially promote and detract from the likelihood of sustained participation. Methods: After an average 7.3 years of follow-up (range 4.9–9.5), Treatment Options for type 2 Diabetes in Adolescents and Youth participants completed a survey examining their perceptions of the benefits and barriers to sustained involvement in the protocol. Results: The most common reasons for staying in Treatment Options for type 2 Diabetes in Adolescents and Youth included having a strong relationship with the medical team, getting study-provided diabetes care, access to free diabetes medicine and supplies, and being part of a large study to learn more about how to care for youth-onset type 2 diabetes. The most commonly endorsed challenges included scheduling conflicts, possibly disappointing others, difficulties getting to study visits, and the occurrence of other medical issues. Conclusions: Similar to other published reports, a supportive relationship with study staff was commonly endorsed as a benefit of engagement in the longitudinal study, suggesting that rapport, staff consistency, and relationship quality are important components of optimal retention. Moreover, our findings suggest the value of trying to remove logistical barriers, such as transportation and scheduling challenges, in order to promote long-term participation in research. Further research is recommended to evaluate factors that contribute to attrition versus retention in an a priori manner within longitudinal studies, especially protocols involving cohorts that are more vulnerable to attrition due to developmental transitions and/or socioeconomic challenges. Additional efforts to optimize quantitative and qualitative measurement of barriers would also help to expand our understanding of how to optimally retain participants in longitudinal protocols.